Project Risk Management of Indah Senada Apartment - Haryogo, Ryan; Wiryono, Sudarso Kaderi (The Indonesian Journal of Business Administration, 2014)
Abstract-PT. ABC as housing developer is planning to build Indah Senada apartment, and they need bank loan in order to build the apartment project. Since they need borrow loan from the bank, managing the Indah Senada apartment project risk is important for PT. ABC themselves and the bank. By managing the risk of the Indah Senada apartment project it is expected that the risk loss can be minimizes and opportunities can be maximized.The context of the risk management in this final project is to manage the external and internal risk factors that can affect to the on time schedule of the Indah Senada apartment project process. And from external, internal and SWOT analysis there are 19 risk factors that might happen and can affect to the on time schedule of the apartment project. And then from risk assessment there are two extreme risk factors priority, 8 high risk factors priority, 6 medium risk factors priority and three low risk factor priorities. And the last from risk treatment there are 6 risk factors that must be doing risk prevention or risk avoidance, two risk factors that must be doing impact mitigation, 8 risk factors that must be doing risk sharing or insurance and three risk factors that can be risk retention.And for implementation planning, the first month of the project schedule is meeting to determine risk treatment planning for each risk factor and the last 23 month of the project schedule is implementation of risk treatment for each risk factor.Â Keywords: Risk Management, Project Management, Apartment Project